Fairy Tale Characters in Shrek : Subversion and New Canon - López González, Rebeca Cristina (Via Panoramica: Revista de Estudos Anglo-Americanos / A Journal of Anglo-American Studies, 2018)
When William Steig wrote in 1990 Shrek! he did not know his 30 colorful pages, filled with rhymes and playful language, would be transformed eleven years later into one of the most successful animated feature films, both for children and adults alike, namely, Shrek (2001). This box office hit led to the production of three more films, Shrek 2 (2004), Shrek the Third (2007) and Shrek Forever After (2010) which have modified the way the classical fairytale canon is understood in the twenty-first century. The entertainment offered by this film is the result of what Raquel Segovia has termed in Spanish transferencia o trasvase (223), which includes translation and adaptation in a process where the original text belongs to a printed means of communication (a children’s storybook in this case) to be subjected to a transference process. This process transforms the literary text into a new audiovisual product. The aim of this paper is to analyze how Dreamworks dealt with this transference process while taking into consideration the concepts of subversion of the classical fairytale canon and rewriting. The latter can be understood thanks to the definition given by André Lefevere: “the adaptation of a work of literature to a different audience, with the intention of influencing the way in which that audience reads the work” (“Mother courage’s cucumbers” 4). Examples extracted from the original fairytale will be contrasted with the work done by Dreamworks where characters subvert the traditional stereotypes and functions described by Vladimir Propp in Morphology of the Folktale.